HAPLOIDENTICAL STEM CELL TRANSPLANTATION FOR SEVERE APLASTIC ANEMIA IN UPFRONT OR RELAPSED/REFRACTORY SETTINGS: A SINGLE-CENTER RETROSPECTIVE STUDY - EH Atta; D Lerner; AP Vilella; LJ Arcuri (Hematology, Transfusion and Cell Therapy)
Introduction: Despite promising results reported by Johns Hopkins, upfront haploidentical stem cell transplantation (haplo-HSCT) using post-transplant cyclophosphamide (PT-Cy) remains an experimental approach. However, the unavailability of horse ATG in Brazil, which appears to be more effective than rabbit ATG, and the ready availability of haploidentical donors renders upfront haplo-HSCT an interesting alternative. Objectives: To report the outcomes of haplo-HSCT in patients with SAA in the upfront and relapsed settings. Patients and Methods: This single-center retrospective study was conducted at Instituto Nacional de Câncer, Rio de Janeiro, Brazil. Seventeen patients with SAA underwent haplo-HSCT between January 2018 and December 2023. There were 12 patients who underwent upfront haplo-HSCT and 5 patients who underwent haplo-HSCT for relapsed/refractory SAA. Donor-specific anti-HLA antibody (DSA) screening test was performed for all cases. Patients with high DSA levels (mean fluorescence intensity (MFI) > 2000) underwent desensitization therapy. Conditioning regimens and graft-versus-host disease prophylaxis included fludarabine, cyclophosphamide plus TBI 400 cGy with PT-Cy, and calcineurin inhibitor plus mycophenolate mofetil. Results: Patients who underwent haplo-HSCT in the upfront and relapsed/refractory settings for SAA were similar regarding: median age (21 vs. 20 years, p = 0.72), female sex (66.7% vs. 80%, p = 0.58), use of bone marrow as graft source (83.3% vs. 16.7%, p = 0.87), total nucleated cell dose (3.96 vs. 3.67 x 108 /Kg, p = 0.57), and pre-HSCT ferritin levels (2170 vs. 1760 ng/mL, p = 0.79). There were more patients with very SAA in the upfront haplo-HSCT group (75% vs. 0%, p = 0.005). Therefore, patients who received upfront haplo-HSCT had a lower pre-transplant absolute neutrophil count (112 vs. 691/μL, p = 0.006). Parents were the most common donors for both upfront and relapsed/refractory haplo-HSCT: 58.3% vs. 80% (p = 0.31), respectively. Although not statistically significant, graft failure was only observed in SAA patients who underwent upfront haplo-HSCT (33.3% vs. 0%, p = 0.14): 2 primary and 2 secondary graft failures. All patients who rejected had low DSA levels (MFI 500 - 1300). The 2-year overall survival (OS) was 75.0% vs. 66.7% in patients who received upfront and second-line haplo-HSCT, respectively (p = 0.50). The 2-year OS was dismal among patients who experienced graft failure (25% vs. 88.9%, p = 0.002). A second haplo-HSCT was performed in 33.3% versus 20% of patients submitted to haplo-HSCT in the upfront and relapsed/refractory setting (p = 0.58). All second haplo-HSCT cases in upfront haplo-HSCT were due to graft failure. The only case of second haplo-HSCT in relapsed/refractory haplo-HSCT was a patient who developed secondary acute myeloid leukemia. Conclusions: The 2-year OS was similar between SAA patients submitted to upfront and second-line haplo-HSCT despite the higher prevalence of very SAA in the former. Graft failure was observed mainly after first-line haplo-HSCT, highlighting the need for improved donor selection and conditioning regimens in such patients. Prospective studies comparing the outcomes between upfront haplo-HSCT and immunosuppressive therapy in countries where horse ATG is unavailable are urgently needed, especially for patients at higher risk of mortality due to severe neutropenia.